The role of NGOs in sustainable tourism in Turkey - Gökçetin, Ayşenur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Given the worldwide importance of NGOs, which are regarded in recent years as the primary advocates and practitioners of sustainable tourism, this research seeks to determine the degree and nature of contribution by selected NGOs in Turkey for establishing and promoting sustainable tourism activities and to inquire their transformative power in terms of sustainable tourism. Activities of NGOs in developed and developing countries might present different patterns and analyzing the case of NGOs in Turkey, which is an emerging economy, might imply a new perspective. With a preliminary NGO database search, relevant NGOs that are involved with sustainable tourism were identified and selected based on four criteria. After a content analysis of NGOs’ websites with regard to their sustainable tourism activities, a semi structured interview was directed to NGO respondents. Afterwards, interviews were coded and results were analyzed in a qualitative manner. It is found that there are differences among directly and indirectly tourism affiliated NGOs in their involvement with sustainable tourism and their transformative power for sustainability and that sustainable tourism has not been established or developed well in Turkey to this day. In a nutshell, it is identified in this thesis that most pressing tourism issues in Turkey are the lack of effective management, environmental destruction and lack of clear tourism planning. Main roles of NGOs to address these issues are found to be raising awareness, conservation of cultural and natural assets as well as involvement in tourism planning.
Keywords: Sustainable tourism.; Sustainable tourism -- Turkey.